PROVISION OF CHERT AS A SOURCE OF SILICONE (SI) FOR THE GROWTH AND YIELD OF RICE (ORYAMMONIUM SULFATE SATIVA L.) TO SUPPORT A SUSTAINABLE CULTIVATION SYSTEM - Kotta, Herry Z.; Mella, W.I. I.; Suwari; Bhuja, Paulus (International Journal of Research -GRANTHAALAYAH, 2020)
A combination of silicon and macro nutrients has been proven to increase rice yield above the average of macro nutrient alone. Chert can contain up to 98% of silicon.Rice field in Timor can be alkaline or non-alkaline in nature. The solubility of SiO2 tends to be higher under acidic soil condition. The use of nitrogen fertilizer can reduce the acidity and hence may increase silicon availability. This research in designed to study the effect of the use of chert powder in combination with urea and ammonium sulfate on rice growth and yield.The study was a pot experiment laid-out based on complete randomized design with nine treatments and three replications. The treatments were control, chert powder 55 kg/ha,chert powder110 kg/ha, urea 100 kg/ha;ammonium sulfate 200 kg/ha,urea 100 kg/ha + chert powder 55 kg/ha,urea 100 kg/ha + chert powder 110 kg/ha, ammonium sulfate 200 kg/ha + chert powder 55 kg/ha, and ammonium sulfate 200 kg/ha + chert powder110 kg/ha. Results showed no significant difference in rice plant height and tillers among the treatments. Beside treatment effect, there was an indication of effect of factors other than treatment effects especially on the non-alkaline pots. It was suspected that the additional effect might be due to the presence of allelophatic substances.Therefore, it is suggested to have a future study on a combined effect of allelophatic substance and treatments assigned to this study to observe such an effect on rice growth and yield.